The Role of Management Accounting Systems in Product Quality Control - Middin, Muslianti; Ratte, Rosalena Belo; Usman, Asri; Mediaty, Mediaty (Formosa Journal of Multidisciplinary Research, 2024)
In an increasingly competitive business world, companies are required to produce quality products. SAM is a formal system that utilizes information to support various company activities. SAM has four main characteristics: broad coverage, aggregation, integration, and timeliness. Product quality control functions to integrate quality maintenance and development so that production and service are more efficient and satisfy consumers. There are three components of SAM in quality control: quality control objectives, quality feedback, and quality incentives. Companies need to control the products they produce to minimize defects. SAM helps present information on product quality and employee performance, as well as managing data into reports that support managers in decision making.